Recent Developments in Seedless Grapevine Breeding - Akkurt, M.; Tahmaz, H.; VeziroÄŸlu, S. (South African Journal of Enology and Viticulture, 2019)
Grapes are one of the most commonly produced fruit crops in the world and are consumed as table grapes, wine grapes and dried grapes. In line with consumer demands, seedlessness continues to be an important feature that increases the chances of marketing grapes. Nearly all of the dried grapes that are offered to the world markets are seedless grapes. In addition, the demand for seedless varieties has increased steadily in the table grape trade over the years. Therefore, the production of new seedless grape varieties with large berries that are suitable for table consumption is one of the important goals of breeding studies in viticulture. In this study, recently bred and released new seedless grape varieties are briefly introduced, seedless grape breeding methods are summarised, and the latest developments in breeding methods are explained.